Using rates of non-adherence to identify opportunities for intervention in outpatient specialty clinics. (21st September 2018) - Cherry, E.; Jolly, J.; Zuckerman, A. D.
Abstract: Background: Adherence to specialty medications is crucial to achieve desired clinical outcomes. Approximately 30–50% of patients on chronic medications are reportedly non-adherent, with up to 50% of non-adherence being clinically appropriate. However, the patients who are non-adherent without clinical reason present an opportunity for the specialty pharmacies to improve adherence leading to optimal outcomes. Identifying disease states at highest risk for nonadherence within specialty populations will provide meaningful outcomes on which specialty pharmacists can focus targeted adherence efforts. Objectives: To utilize pharmacy claims data to determine and analyze rates of non-adherence in outpatient specialty clinics. Methods: This is a single-center, retrospective pharmacy claims analysis. Claims data for specialty medications at Vanderbilt Specialty Pharmacy (VSP) from November 2016 to December 2017 were used to calculate proportion of days covered (PDC). Clinical categories were assigned to patients in the dispensing system used at VSP, and included cystic fibrosis, dermatology, endocrinology, hepatitis C, idiopathic pulmonary fibrosis, infectious diseases, irritable bowel disease, lipid disorders, neurology, multiple sclerosis, oncology, pulmonary arterial hypertension, and rheumatology. Also included were pediatric categories. Patients were included if they received at least three fills from VSP. Nonadherence was defined as a PDC of <80%. Rates of non-adherence by clinic were then calculated by dividing the number of non-adherent patients in a clinic by the total amount of patients in the clinic. Results: A total of 7307 records were included from 18 clinical areas. The average PDC for all included patients was 93.1%. The overall non-adherence rate was 12.5%. The highest rates of non-adherence were in pediatric oncology and endocrinology (25.6% and 22.2%), and adult rheumatology (15.8%). The lowest rates of non-adherence were found in pulmonary arterial hypertension, hepatitis C, and interstitial pulmonary fibrosis (3.4%, 3.7% and 4.2%, respectively). Conclusions: Our results show overall high numbers for PDC among our cohort, however also highlight areas for improvement. Using a similar method, specialty pharmacies may identify patient populations that are prime candidates for targeted adherence interventions. Understanding that up to 50% of non-adherence is intentional, there remains a significant opportunity to focus on specific clinics and patients to improve outcomes of specialty medications.